2017
DOI: 10.3390/md15070225
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of Tetrodotoxin Modeled in a Porcine Renal Proximal Tubule Epithelial Cell Line, LLC-PK1

Abstract: This study examined the urinary excretion of tetrodotoxin (TTX) modeled in a porcine renal proximal tubule epithelial cell line, LLC-PK1. Time course profiles of TTX excretion and reabsorption across the cell monolayers at 37 °C showed that the amount of TTX transported increased linearly for 60 min. However, at 4 °C, the amount of TTX transported was approximately 20% of the value at 37 °C. These results indicate that TTX transport is both a transcellular and carrier-mediated process. Using a transport inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
(50 reference statements)
2
8
0
Order By: Relevance
“…Furthermore, the PBK modeling data of this study revealed that up to 86% of TTX clearance in the kidney could be ascribed to active transport by the proximal tubule cells. This active transport of TTX was previously also demonstrated in the renal proximal tubule cell line LLC-PK1 ( Matsumoto et al , 2017 ). In this in vitro study, TTX was shown to be primarily transported by the organic cation transporters and the organic cation/carnitine transporters.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Furthermore, the PBK modeling data of this study revealed that up to 86% of TTX clearance in the kidney could be ascribed to active transport by the proximal tubule cells. This active transport of TTX was previously also demonstrated in the renal proximal tubule cell line LLC-PK1 ( Matsumoto et al , 2017 ). In this in vitro study, TTX was shown to be primarily transported by the organic cation transporters and the organic cation/carnitine transporters.…”
Section: Discussionsupporting
confidence: 73%
“…The glomerular filtration (GF) was added to the model according to the equation: GF = GFR × (CVK × fub in vivo ), where GFR is the GF rate, which is 5.2 ml/min/kg bw for rat and 14 ml/min/kg bw for mouse ( Walton et al , 2004 ), CVK is the concentration of TTX in the kidney compartment and fub in vivo is the fraction of TTX unbound in the in vivo situation. As mentioned by Matsumoto et al (2017) , TTX seems to be a substrate for some active transporters in the proximal tubule cells in the kidney. Since it is unknown which transporter has the highest contribution it was decided to work with an estimated apparent overall V max and K m ; 1 V max and 1 K m for all transporters involved.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…Upon oral exposure, TTX absorption is rapid but incomplete (around 7%), there is hardly metabolism of TTX in the liver and with its highly hydrophilic characteristic TTX is predominantly excreted via the urine (Hong et al 2017;Hong et al 2018). Due to the charges on the molecule it is foreseen that excretion of TTX, next to glomerular filtration, will proceed via active transporters in the renal proximal tubule epithelial cells, most likely the OCT2 transporter with a lesser contribution of OCTN1/2, MATE and OATs (Matsumoto et al 2017). Using PBK modelling the active transport of TTX will be further unravelled.…”
Section: Tetrodotoxin (Renal Excretion)mentioning
confidence: 99%